Pengaruh Posisi Dilatasi Terhadap Gaya Dalam Pada Denah Bangunan Berbentuk U - Aryanti, Riza (Universitas Andalas, 2024)
Most of Indonesia is located in an active fault zone. West Sumatra is included in the area crossed by the Sumatran fault line which has a high potential for earthquakes. One of the impacts of earthquakes is building damage. When an earthquake occurs, buildings on the earth's surface vibrate. One of the design methods for planning tall buildings with an asymmetrical floor plan to strengthen and increase the structural resistance to earthquakes is to provide dilation to the building. This analysis was carried out on a building with a U-shaped layout located in a high-risk earthquake area, namely in Padang City, West Sumatra. The purpose of this study was to determine the effect of the dilation position on the forces in the structural components. The analysis was carried out on three structural models: the first model is a structure without dilation, the second model is a structure with dilation in the x direction, and the third model is a structure with dilation in the y direction. The earthquake data used refers to the Padang City earthquake spectra design data. The results showed that the second model produced the smallest internal force value.